Characterization of ultra-low permeability tight sandstone reservoir properties and criteria for hydrocarbon accumulation in Chang 6 member, Huaqing area, Ordos basin - Liao, Jianbo; Hong, Liang; Li, Zhiyong; Tan, Kaijun; Zhao, Leyi; Yang, Jun; Yu, Pinghui (Frontiers in Earth Science, 2022)
How to accurately predict hydrocarbon enrichment and high-yield areas in ultra-low permeability sandstone reservoirs is a hot spot in petroleum geology. Taking the Chang 6 Member of the Yanchang Formation in the Huaqing Area, Ordos Basin as an example, the quantitative characterization and classification criteria of ultra-low permeability sandstone reservoir properties are systematically studied. The research results show that the seismic reflection characteristics of the Chang 6 Member show multi-stage wedge progradation characteristics, reflecting the sedimentary characteristics of the end of the delta front. The maturity of the minerals in the Chang 6 Member sandstones in the study area is very low, it indicates a low degree of transformation of sediments. Three types of sand bodies, namely sandy debris flow, turbidite, and slump rock sand bodies, were identified in the Chang 6 Member of the Yanchang Formation. The pore types of the Chang 6 Member in the study area include intergranular pores, dissolution pores (feldspar, detrital dissolution pores), and intercrystalline pores. Among them, the intergranular pores and feldspar dissolution pores are the most important storage spaces. The study also found that the test oil production is highly correlated with the cumulative thickness of the massive sandstone segments. Therefore, massive sandstone (sand debris flow) is the main contributor to oil well production, and its distribution directly controls the accumulation of oil reservoirs and the high production of oil wells. In addition, geological parameters affecting reservoir enrichment evaluation were analyzed, which include permeability, oil layer thickness, resistivity, and reservoir penetration rate. Finally, the evaluation criteria for hydrocarbon enrichment in the Chang 6 Member were formulated by the analysis of dominant facies, lithologic assemblages and electrical properties.